Social Media (YouTube) Content Analysis to 5 Indonesian’s Super Priority Destination - Primastahta, Candraning Koes; Widyaninggar, Cakry Lientang; Mani, La (E-Journal of Tourism; Volume 9 Number 2 (September 2022), 2022)
The COVID-19 pandemic directly provided a huge answer to leaders. Therefore, all countries and their respective countries must have various competent policies or strategies to overcome the impact of the COVID-19 pandemic, and of course these policies or strategies are implemented and adapted to developing conditions, one of which is Virtual Tourism innovation. A tourist activity that can be enjoyed anywhere and anytime, because it only requires an internet network, social media platforms and gadgets. With the emergence of this innovation, it is hoped that it can maintain tourism and reduce the impact of the COVID-19 pandemic because it can be enjoyed at home. The purpose of the study was to determine the implementation of Government Policies in 5 Super Priority Destinations (Lake Toba, Labuan Bajo, Borobudur, Mandalika and Likupang) through social media (YouTube) with a comparative case study of promotions conducted at Wishnutama and Sandiaga's tenure. Quantitative descriptive research method using YouTube videos collected since January 1st. 2020 to February 4, 2022. The number of samples used is 65 videos that meet the requirements of 5 Super Priority Destinations. The testing tool used is Nvivo 12 Pro with several stages of Node creation to a total comparison of the subject and object of research. The result of this study is that Sandiaga is more communicative in promoting 5 Super Priority Destinations with various new programs such as video content created and consistent upload schedules. Both Wishnutama and Sandiaga have the same significant focus on the Lake Toba destination. The messages included in the uploaded YouTube videos are dominated by Communication Policy messages as well as informative messages from each destination. In addition, to support the two messages also use Advertising, Persuasive and Educational messages. Keywords: content analysis; communication policy; 5 super priority destinations; tourism promotion; youtube.